A concern about younger drivers in Perth - Ebrahim, Z.; Nikraz, Hamid (2015)
© 2015 WIT Press. This paper highlights the concerns about younger drivers in Perth. Evidence suggests that this group of drivers were speeding at different levels particularly the highly excessive. Despite 60 km/h being considered a higher speed limit than the other two limits under this study, it was found that younger drivers are speeding and taking higher risks on roads that belong to the 40 and 50 km/h speed limits. The On the spot' detection found roads, which belong to 50 km/h, were also of concern. Male drivers were dominating the speeding on roads for the three speed limits roads studied. Pedestrian crash data also supported this evidence in concluding that the leading number of drivers who hit pedestrians belongs to this younger age group. Speeding and pedestrian crashes on 40 km/h on non-school zone roads are also examined and discussed. It is recommended that along with enforcement, two levels policy need to be targeted in parallel. First, a safety audit to the 50 and 60 km/h limits as a comprehensive municipal programme that may lower the limits to a safer speed on these roads needs to be adopted. Second, authorities may focus on younger drivers' licence regulations in terms of speeding violations and accidents history and real scenario training that relates to that age group. Such policy direction may bring high returns in sustaining safer roads.